Rare but heard: using asynchronous virtual focus groups, interviews and roundtable discussions to create a personalised psychological intervention for primary sclerosing cholangitis: a protocol - Martine Walmsley; Veronica Ranieri; Eilis Kennedy; Doug Thorburn; Kathy McKay (BMJ Open, 2019)
Introduction Primary sclerosing cholangitis (PSC) is a rare and chronic disease characterised by inflammation and fibrosis of the liver’s bile ducts. There is no known cause or cure for the illness, which often progresses to end-stage liver disease requiring liver transplantation. Symptoms of PSC can be very burdensome on those living with the illness, leading to restrictions in daily living, as well as a greater risk of colorectal and biliary tract cancers. Limited voices from lived experience suggest that living with PSC can cause considerable psychological distress. This study, therefore, aims to explore how the illness impacts the psychological well-being of those living with the illness, and those supporting them. It also aims to create a personalised psychological intervention to support all groups.Methods and analysis This project will take a layered qualitative approach to understanding the ways in which people experience living with PSC within their day-to-day lives. There will be two stages to this study, which will pilot a unique methodological process using online resources. The first stage will consist of asynchronous virtual focus groups (AVFGs) with those living with PSC and those who provide support for those diagnosed with PSC, and narrative interviews with both groups and health professionals. Both the AVFGs and the narrative interviews will be analysed using thematic narrative analysis. The second stage will comprise a roundtable discussion where the researchers and health professionals will devise a personalised psychological intervention to help to support those living with PSC and their supporters. The study duration is expected to be 18 months.Ethics and dissemination The proposed study has been approved by the UK Health Research Authority and London—Queen Square Research Ethics Committee as application 18/LO/1075. Results from the AVFGs and the narrative interviews will be submitted for peer-reviewed publication. The findings of the study will also be presented nationally to PSC and medical communities, and a summary of the findings will be shared with participants.